2014
DOI: 10.1177/1471301214532643
|View full text |Cite
|
Sign up to set email alerts
|

The provision of assistive technology products and services for people with dementia in the United Kingdom

Abstract: In this review we explore the provision of assistive technology products and services currently available for people with dementia within the United Kingdom. A scoping review of assistive technology products and services currently available highlighted 171 products or product types and 331 services. In addition, we assimilated data on the amount and quality of information provided by assistive technology services alongside assistive technology costs. We identify a range of products available across three areas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
123
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(128 citation statements)
references
References 44 publications
2
123
0
3
Order By: Relevance
“…The section on technology development was based on expert opinion and relevant literature, among other previous reviews of taskforce members [23,24]. For the sections on usability, effectiveness and cost-effectiveness, and ethical issues, separate literature searches were conducted in PubMed, CINAHL, PsycINFO, and Embase databases.…”
Section: Methodsmentioning
confidence: 99%
“…The section on technology development was based on expert opinion and relevant literature, among other previous reviews of taskforce members [23,24]. For the sections on usability, effectiveness and cost-effectiveness, and ethical issues, separate literature searches were conducted in PubMed, CINAHL, PsycINFO, and Embase databases.…”
Section: Methodsmentioning
confidence: 99%
“…Concerning financial access from a consumer perspective, cost of technology must include acquisition and rental costs, plus support and maintenance costs. AT services are subject to major variations in pricing in a mixed economy of multiple dementia care providers, including primary care, local authorities, private companies and local or national resources dedicated to assistive technologies (Gibson et al, 2016). Solvency of consumers is key to facilitate purchase of AT, and can partly be compensated by public policies.…”
Section: Design and Development Of Technologies For People With Dementiamentioning
confidence: 99%
“…A recent review of commercially available AT for people with dementia identified 171 products and 331 services, which can be grouped in products used "by" people with dementia, "with" them or "on" them (Gibson G et al, 2016). More and more, people with dementia express themselves on blogs: most of them use non-specific technologies, such as smartphones or computers, generally with a positive experience.…”
Section: Dementia As a (Potential) Disabilitymentioning
confidence: 99%
“…This could include consumer information regarding AT and where to purchase it, which may be particularly relevant where a local authority is not able to provide for a particular individual [11,17]. Such information regarding private AT is reported to be in short supply -which is a potential barrier to any consumer market, if the potential customers are unsure of where to purchase such products [2,3,15,16] [6, p.81] However, it has been recognised that currently health and social care professionals themselves are not always aware of services pertaining to their patient's needs [10,18,19] therefore the information needs of clinicians must also be considered. As well as availability of information, the type, source, accessibility, and quality of information needs to be considered -information which is available yet inaccessible does nothing to reduce barriers to AT uptake.…”
Section: Lack Of Access To Information Regarding Atmentioning
confidence: 99%